Prognostic role of hemostasis-regulating genetic factors and their interaction with conventional risk factors at the early stages of coronary heart disease development - E. Yu. Andreenko; L. M. Samokhodskaya; A. V. Balatskyi; P. I. Makarevich; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To investigate the prognostic role of selected single nucleotide polymorphisms in hemostasis-regulating genes and to clarify their interaction with conventional risk factors, RF (smoking, arterial hypertension (AH), hypercholesterolemia (HCH), obesity (O)) at the early stages of coronary heart disease (CHD) development, with or without subsequent myocardial infarction (MI). Material and methods. The study included 977 men aged 20–55 years: 375 CHD patients (189 and 186 with or without previous MI, respectively) and 602 individuals without cardiovascular disease (CVD). Exclusion criteria were diabetes mellitus and impaired glucose tolerance. The authors analysed the polymorphisms of thrombocyte receptor genes GPIa (C807T) and GPIIIa (PLA1/PLA2); coagulation and fibrinolytic protein genes for factor VII (R353Q) and factor XIII (V34L); and the plasminogen activator inhibitor-1 (PAI-1) 4G/5G polymorphism. The association of these polymorphisms with conventional RF (smoking, AH, HCH, and O) was also investigated. To identify genetic variations, a restriction fragment length polymorphism assay, allele-specific assay, and fluorescence primer-probe assay were used. Results. Increased CHD risk was associated with the TT genotype of GPIa (p=0,0001; OR=10,2). The LL genotype of FXIII (p=0,03; OR=0,48) and QQ genotype of FVII (p=0,01; OR=0,12) were linked to reduced CHD risk. The combination of FXIII L allele and FVII Q allele was associated with a lower MI risk in CHD patients (p=0,03; OR=0,33). In participants with HCH, the PLA2/PLA2 genotype of GPIIIa was linked to increased MI risk for CHD patients (p=0,01; OR=6,0). Conclusion. The algorithm for predicting the genetic CHD risk may incorporate the assessment of the genetic polymorphism of GPIa (C807T), GPIIIa (PLA1/PLA2), factor XIII (V34L), and factor VII (R353Q). The study results did not confirm the negative effect of the PAI-1 gene 4G/5G polymorphism on CHD risk.